Rancang Bangun Mesin Peniris Minyak Untuk Proses Produksi Abon Ikan - Limbong, Ishak S.; Doni, Hendra Bin; Koehuan, Verdy A. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
Draining oil on fried foods is traditionally seen as less than optimal. In addition, it takes a longer time, however, the oil content in the food is still relatively high so that the food becomes less durable. This study aims to design and build a prototype of a rotary oil draining machine that utilizes centrifugal force which is able to drain oil faster with better results than the traditional method. The advantage of the design of the oil draining machine in this study is that the materials used to manufacture this machine are quite cheap and more effective than traditional draining machines. The stages of making this machine consist of the stages of designing, manufacturing, assembling and testing the machine. This machine is designed and built with specifications: 55 cm high, 78.5 cm long, 43.5 cm wide and the test results of this shredded fish oil draining machine reach a capacity of 29.50 kg/hour